(untitled) (RIAF. International Journal of Physical Activity, 2025)
This study aims to develop local cultural identity in the university context through Extension University activities based on traditional games. The research, using a mixed approach, was based on interviews with specialists, participant observation of game workshops, and analysis of historical documents. A program was designed and implemented that integrated traditional games into Extension University activities, promoting their practice and participant satisfaction. The program was based on the premise that traditional games, in addition to their physical benefits, serve as educational resources that foster knowledge of local culture and its importance for identity. The research results showed that the recreation of traditional games in the university setting significantly contributed to the construction of a stronger and more relevant cultural identity. The research highlights the importance of integrating local culture into university education through practical activities such as traditional games and emphasizes the need to develop intervention strategies that allow for the effective and sustainable implementation of these types of initiatives.